EVALUASI PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) KEPADA MASYARAKAT DI DESA DAUH PURI KAJA KOTA DENPASAR - Putra, I Kadek Indra Pradika; Antarini, Lilik; Putra, I Putu Adi Permana (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The program (BLT-DD) is an assistance program issued by the government with the aim of minimizing the gap that occurs in the underprivileged community in each village. This research was conducted to determine the Evaluation of the Village Fund Direct Cash Assistance Program (BLT-DD) to the community in Dauh Puri Kaja Village, Denpasar City. This study uses a qualitative research approach method with a descriptive approach. In this study, 6 evaluation indicators were used, namely; Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. The data of this research was obtained from observations, interviews with 5 informants, documentation, and other secondary data. Based on the results of the interview, it shows that the implementation of the program (BLT-DD) to the community in Dauh Puri Kaja Village, Denpasar City has been implemented quite well in implementing the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration (PDTT) of the Republic of Indonesia Number 13 of 2023 Regarding Operational Guidelines on the Focus on the Use of Village Funds for Program Implementation (BLT-DD) in 2024. It can be said that this is because it is proven that the community feels relieved of the funds given every month to finance family needs. The implementation has shown the accuracy of the assistance targets, the evenness of assistance that the village is able to distribute to the underprivileged, and the government is always responsive to complaints or problems reported by the community. However, there are still obstacles such as data problems from the central government and villages that are often different regarding Beneficiary Families (KPM) data. There was a delay in the disbursement of aid at the beginning of the year. Complaints about the implementation of socialization are still lacking, because it is carried out every six months. As well as the use of human resources that are still somewhat insufficient to assist the implementing party in running the program (BLT-DD). The advice that can be given is that the government always coordinates to ensure that the data of the parties (KPM) is correct and valid, there needs to be regular and scheduled socialization carried out by the village government so that information is evenly received by all communities. The village government needs to pay attention to the assignment of human resources with the required number so that the report work is completed on time.